Self-perception of ethically dubious practices: a study with Human Resource managers - Silva, V. H.; Duarte, A.P.; Simões, E.; Neves, J. (EAWOP 2017 Congress, 2017)
Previous studies suggest that corporate social performance of organizations influences their attractiveness as a workplace. The ethical reputation is a construct positively related to corporate social responsibility (CSR) which could be more or less salient according the centrality that moral values assume in individual identity. The main goal of this research was to investigate the relationships among CSR, attractiveness, ethical reputation and moral identity using a moderated mediation analysis. In this study CSR perception was manipulated in order to observe its effect on organizational attractiveness through the mediating effect of ethical reputation moderated by moral identity. Participants (n = 222) were randomized by two experimental conditions, responding to an electronic questionnaire containing the description of an organization that met (high involvement condition) or not (low involvement condition) a set of CSR practices, followed by questions about other variables of interest. The results show that CSR affects directly and indirectly, through ethical reputation, the evaluation of the organization as a future workplace and the power of this relationship depends on moral identity. In practical terms, this means that in the “war for talent”, organizations can make use of information about their corporate social performance and ethical reputation as a tool to attract potential candidates, alongside the traditional information on organizational attributes and function characteristics